MARKETING STRATEGY MODEL OF SMALL BUSINESS : STUDY ON FOOD SPECIALTIES CENTER IN BENGKULU - Syaiful Anwar AB (Jurnal Ilmiah Ekonomi Bisnis, 2012)
Small businesses have been interested topics for researchers. This topic is interested as small businesses have been showing the capability to survive on economics difficulties. The objective of the research is to asses the capability of Bengkulu District in improving small Business strategy. Policies in this case are analyzed in order to provide the answer to the objective. Effectiveness of policies which were gone out during 2005 up to 2010 was evaluated. The method is known as policy analysis.Results of the study showed that market segmentation based on area policy plays as important element of motivation improvement of market strategy development. Bengkulu District Government policy related to manage special foods centre is possible to be used as benchmark to others region in which integrated management system, new innovation, and responsive towards new development.Keywords: small business, marketing strategy, food center, policy analysis Penelitian yang mengkaji unit usaha kecil sudah banyak dilakukan. Penelitian menjadi menarik karena usaha kecil terbukti bertahan dalam kondisi perekonomian yang sulit. Tujuan penelitian ini adalah untuk mengkaji kemampuan daerah Bengkulu dalam pengembangan strategi usaha kecil. Metode analisis yang digunakan adalah analisis kebijakan dari tahun 2005 sampai tahun 2010. Hasil penelitian menunjukkanfungsi kebijakan segmentasi pasar berdasarkan wilayah berperan sebagai elemen penting bagi daerah Bengkulu dalam peningkatan motivasi pengembangan strategi pemasaran. Kebijakan pemerintah daerah Kota Bengkulu dengan penetapan sentra makanan khas dapat ditiru daerah lain dalam strategi pengembangan usaha kecil dengan menerapkan sistem manajemen terpadu, ide baru, dan tanggap terhadap isu yang berkembang saat ini.Kata kunci: usaha kecil dan strategi pemasaran, pusat makanan, analisis kebijakan